VALUATION OF THE NUTRITIONAL MATRIX BY PHYTASE AND SOY GUM IN THE DIET FORMULATION FOR BROILER CHICKENS - Nascimento Rostichelli, Luiz Gustavo; De Laurentiz, Antonio Carlos [UNESP]; Filardi, Rosemeire Da Silva [UNESP]; De Pedro Souza, Rosemary Pereira [UNESP]; De Paula Carlis, Matheus Sousa (Univ Fed Rural Semi-arido-ufersa, 2020)
The study was carried out with the objective of evaluating whether the valorisation of the nutritional matrix by the addition of the enzyme phytase and soy gum, in isolation or in association in the formulation of broiler chicken diets compromises the performance in the phase of 7 to 42 days of age and can be economically viable. Seven hundred 7-day-old male Cobb 500 broiler chicks were distributed in a completely randomised design consisting of seven treatments and five replications of 20 birds. The treatments consisted of a standard diet and six other diets whose matrix values of phytase and gum were valued, either alone or in combination, in the formulation of the diets. The individual valuation of the nutritional matrix of the phytase and soy gum in the formulation of feed for broiler chickens did not compromise the zootechnical performance of the chickens; however, only the valuation with phytase proved economically viable, since the inclusion of the gum and its valuation did not contribute to a reduction in the production cost or gross margin compared to a standard diet.
Keywords: Additive; Available phosphorus; Emulsifie; Lecithin; Metabolisable energy